SCALE AND SERPENT TWO-GROUP CROSS-SECTION DATA GENERATION - Ondřej Novák; Jan Frýbort; Lubomír Sklenka; Jan Rataj; Ondřej Chvála (Acta Polytechnica CTU Proceedings, 2018)
In this work, VVER fuel assembly is calculated using two different codes - Serpent and SCALE. Multiplication factor and several two-group macroscopic parameters including scattering cross-section, fission cross-section, total cross-section and diffusion coefficient were studied. In addition to this, fuel isotopic composition dependency on burnup was calculated as a part of this study. Obtained data are compared and differences are discussed. Both codes provides similar results for all studied parameters.